IMPLEMENTATION OF PROJECT-BASED LEARNING IN IMPROVING THE CREATIVITY OF WRITING JAPANESE ESSAYS IN THE SAKUBUN COURSE - Utari, Retno; Sukmara, Rina; Septiany, Nia (Vocational College of Diponegoro University, 2024)
The aim of this research is to find out whether the application of the Project-based Learning (PjBL) model can increase creativity in writing Japanese essays in the Sakubun course. The problem to be investigated in this research is related to improving the ability to write essays in Japanese with students' creativity in composing Japanese sentences. The form of research used is an experimental equation with a pretest – post-test design, namely by measuring how much influence one variable has on another variable. To measure the ability to write Japanese essays, this is done through tests, questionnaires and observations. The data analysis technique used in this research is a form of quantitative data analysis which is carried out to analyze data obtained from implementing the Project-Based Learning (PjBL) learning model by carrying out normality tests, homogeneity tests. Next, the results of the two tests are used to test the effectiveness of the learning model applied.